Graphene oxide-FePO4 nanocomposite: Synthesis, characterization and photocatalytic properties as a Fenton-like catalyst. Issue 6 (15th April 2018) - Zhou, Hu; Yue, Xiaoyang; Lv, Hongwei; Kong, Lirong; Ji, Zhenyuan; Shen, Xiaoping
Abstract: Graphene has received much attention to develop efficient photocatalysts on account of its unique two-dimensional network structure, excellent chemical stability as well as interesting functionalities. Herein, a two-phase self-assembly strategy was applied to prepare graphene oxide (GO)-FePO4 nanocomposites. The resulting products were characterized by XRD, TEM, EDS, IR and UV–vis spectroscopy. The GO-FePO4 materials can act as Fenton-like catalysts and display improved photocatalytic activities compared to pure FePO4 in the degradation of methylene blue under simulated sunlight irradiation. The proposed strategy can be extended to produce graphene-based nanocomposites with various functionalities for the environment protection and energy development.